Molecular forms of natriuretic peptides in heart failure and their implications. Issue 6 (17th May 2009) - Xu-Cai, Ye Olivia; Wu, Qingyu
Abstract : Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are important biomarkers in the diagnosis and risk stratification for heart failure (HF). These peptides are synthesised as inactive precursors, pro-ANP and pro-BNP, which are converted to biologically active 28 amino acid ANP and 32 amino acid BNP, respectively. Most immunoassays currently used in the clinical setting, however, do not determine precise molecular forms of these natriuretic peptides, which may vary depending on the pathophysiological state of HF. Analysis from chromatography-based studies reveals that in HF inactive pro-ANP and pro-BNP forms often predominate. This indicates that the bioactive forms of natriuretic peptides may not be processed proportionally in patients with advanced HF. Distinguishing the bioactive natriuretic peptides from their inactive forms in plasma may help to define the role of these peptides in the pathogenesis of HF and provide new insights into the treatment of the disease.